2006
DOI: 10.1128/aem.00233-06
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Monitoring of the Fecal Microbiota of Healthy Human Subjects during Administration of Lactulose and Saccharomyces boulardii

Abstract: Diet is a major factor in maintaining a healthy human gastrointestinal tract, and this has triggered the development of functional foods containing a probiotic and/or prebiotic component intended to improve the host's health via modulation of the intestinal microbiota. In this study, a long-term placebo-controlled crossover feeding study in which each subject received several treatments was performed to monitor the effect of a prebiotic substrate (i.e., lactulose), a probiotic organism (i.e., Saccharomyces bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 47 publications
7
70
0
2
Order By: Relevance
“…A number of studies have indicated that an individual's gut microbiota can have a relatively stable community composition over a period of months to years (36,49,57,62). These observations have led to the conclusion that the community of microbes in the gut is relatively resistant to perturbation by various ecological stressors.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have indicated that an individual's gut microbiota can have a relatively stable community composition over a period of months to years (36,49,57,62). These observations have led to the conclusion that the community of microbes in the gut is relatively resistant to perturbation by various ecological stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Two molecular techniques, PCR-DGGE and real-time PCR, were combined to achieve a detailed picture of vaginal ecology under normal and abnormal conditions. This integrated approach has been recently proposed for monitoring the effect of prebiotics, probiotics, and symbiotics on the fecal microbiota of healthy humans (37). Consistent with data from previous studies (4, 10, 12, 24, 41), our DGGE data showed that the vaginal bacterial floras in healthy women were stable over time and dominated by a single species or group of closely related species of Lactobacillus (L. iners, L. acidophilus, L. gasseri, and L. vaginalis).…”
Section: Discussionmentioning
confidence: 99%
“…8 Lactulose therapy does not significantly change microbial composition in healthy individuals using culture-independent techniques. 28 Our group evaluated change in microbiota after overt HE therapy was initiated and found that the relative reduction in autochthonous taxa continued despite lactulose therapy. 17 However a systems biology analysis of systematic lactulose withdrawal showed that selected patients have overt HE recurrence once lactulose is withdrawn.…”
Section: Mhe Therapymentioning
confidence: 99%